DENTAL FINDINGS IN MARFAN SYNDROME: A CASE REPORT - Büşra BOSTANCI; Emre KORKUT; Nimet ÜNLÜ (Journal of Istanbul University Faculty of Dentistry, 2017)
Marfan syndrome is an autosomal dominant disorder of connective tissue primarily characterized with anomalies affecting the musculoskeletal system, the cardiovascular system and the eyes. It has been suggested that early diagnosis of the syndrome is important, because of the risk of infective endocarditis. A 7-year-old female was referred to our clinic, with a chief complaint of dental crowding in the anterior region of mandible. It was observed that the patient needed multiple treatments based on detailed clinical and radiographic examinations. The treatment was carried out with antibiotic prophylaxis an hour prior to her appointment considering her profound caries. The patient was advised to visit regularly for follow up and she was referred for orthodontic evaluation.